Mosaic PRKACA duplication causing a novel and distinct phenotype of early-onset Cushing's syndrome and acral cutaneous mucinosis. Issue 6 (24th November 2022) - McGlacken-Byrne, Sinéad M; Abdelmaksoud, Ashraf; Haini, Mohammad; Palm, Liina; Ashworth, Michael; Li, Juan; Wang, Wei; Wang, Xiumin; Wang, Jian; Callaghan, Bridget; Kinsler, Veronica A.; Faravelli, Francesca; et al.
Abstract : Genetic alterations within the cAMP/protein kinase A (PKA) pathway result in a spectrum of adrenocortical disorders. Implicated genes include GNAS, PDE8B, PDE11A, PRKAR1A/B, and PRKACA. To date, pathogenic somatic PRKACA variants and germline PRKACA copy number gain have been associated with the development of cortisol-secreting adrenocortical adenomas and bilateral adrenal hyperplasia, respectively. While perturbations within the PRKAR1A gene are known to cause Carney complex, PKRACA mutations are rarely associated with an extra-adrenal phenotype. We describe a mosaic PRKACA duplication in an infant who presented with a Carney-like complex at the age of 3 months with bilateral non-pigmented micronodular adrenal hyperplasia, severe early-onset Cushing's syndrome, and distinct acral soft tissue overgrowth due to cutaneous mucinosis. This represents a novel manifestation of PRKACA disruption and broadens its extra-adrenal phenotype. It suggests that the Cushing's syndrome phenotypes arising from somatic and germline PRKACA abnormalities likely exist on a spectrum. We emphasise the importance of ascertaining a genetic diagnosis for PRKACA- mediated disease. Significance statement: We describe a mosaic PRKACA duplication in a young infant who presented with a Carney-like complex: bilateral non-pigmented micronodular adrenal hyperplasia, severe early-onset Cushing's syndrome, and distinct acral soft tissue overgrowth due to cutaneous mucinosis. This represents a novel manifestation of PRKACA disruption and broadens the extra-adrenal phenotype of PRKACA-associated Cushing's syndrome. Our data suggest that Cushing's syndrome phenotypes arising from somatic and germline PRKACA abnormalities can exist on a spectrum. We emphasise the value of ascertaining a genetic diagnosis for PRKACA-mediated adrenal and extra-adrenal disease to guide individualised and targeted care.